(untitled) (Journal of Monno Medical College, 2026)
Background: Acne is a common dermatological disorder of teen age group. There are different modalities of topical and systemic treatments are available to manage this disease. Objective: The purpose of the present study was to evaluate the efficacy and safety of Adapalene 0.1% gel in comparison to Benzoyl Peroxide (BPO) 2.5% gel for the treatment of mild to moderate acne vulgaris. Methodology: This single centered randomized controlled trial was conducted in the Department of dermatology and venereology Tairunnesa memorial medical college Hospital, Tongi, Gazipur, Bangladesh from October 2023 to April 2024 for a period of six month. A total number of sixty patients of clinically diagnosed acne vulgaris were primarily selected and randomly divided into two equal group (group-A and group-B). Group A was given adapalene 0.1% gel for 12 weeks & Group B was given BPO 2.5% once daily in the evening for same duration. Patients were clinically assessed at baseline and at week 4, 8 and 12. At each visit, the investigator rated, scaling, erythema, dryness, burning, pruritus on a scale ranging from 0 (none) to 3 (severe). Adverse events were evaluated at each visit. Results: A total number of 60 patients were recruited after fulfilling the inclusion and exclusion criteria. Among them predominant age group was 20 to 24 years which were 27 (45.0%). Male: female ratio was 1:2.52. 51(85%) patients had oily skin type and 9(15%) had dry skin type. Adapalene 0.1% gel was significantly more effective than BPO 2.5% gel, with significant differences in total lesion counts observed as early as 4 weeks of treatment. Adverse event frequency and cutaneous tolerability profile was significantly favorable for adapalene gel in the treatment of acne vulgaris. Conclusions: Once daily Adapalene gel provides significantly greater efficacy and safety for the treatment of mild to moderate acne vulgaris compare to Benzoyl Peroxide gel. Journal of Monno Medical College, June, 2025; 11(1) : 54-59